Development of a weather control indication chart: Development of a weather control indication chart - SCHULZE-NEUHOFF, H. (MAUSAM, 1979)
A weather-control indication chart has been developed. Colour-steps indicate the synop weather at the Sites of the weather-stations on the chart. This way a fast and synoptic geographic dis tribution of the zones of weather (ww), wind, temperature and visibility is obtained.